A cross-sectional comparison of annual training characteristics between junior, developmental, and elite-level biathletes - Solli, G. S.; Engdahl, J.; Tønnessen, E.; Sandbakk, Ø.; Talsnes, R. K. (International Journal of Sports Physiology and Performance, 2025)
Purpose: To compare annual training characteristics and periodization of physical training and shooting between junior, developmental, and elite-level biathletes.